Penetapan dan Penerapan Peraturan Spesifik untuk Meningkatkan Kedisiplinan Siswa Kelas VIII SMP ABC Cikarang [Making and Applying Specific Rules for Hand Raising Before Speaking to Improve Discipline of Grade VIII Students at a Junior High School during Biology Class] - Eimenina Saemara Pelawi; Juniriang Zendrato; Lastiar Roselyna Sitompul (Universitas Pelita Harapan, 2016)
It was discovered that during the process of learning biology, grade VIII students at SMP ABC in Cikarang lacked discipline which distrupted the ability of the class to study conducively. To solve this problem, the researcher implemented a specific rule which was